Breaking Barriers: How the Pandemic Bridged the Academic Achievement Gap in Rural and Urban Schools - Y.D. Kersha; O.V. Nedosyp; E.I. Piotukh (Moscow State University of Psychology and Education, 2023)
The article examines the impact of the COVID-19 pandemic on the dynamics of academic achievement in schools in the Novosibirsk region over the period of 2017–2022. Using data on individual Basic State Examination results of grade 9 students, the study applies multilevel regression modelling to examine the differential impact of the COVID-19 pandemic on urban and rural schools. Contrary to previous studies which predicted that rural students would be most affected, the results were unexpected. When analysing the academic performance of students in the overall sample, no significant differences were found between the years: on average, the pandemic had no effect on academic performance in the region. However, assessing the differential effect according to the type of settlement in which the school was located revealed atypical trends: urban schools experienced a slight decrease in academic achievement after the pandemic, while rural schools experienced an increase. Notably, the year of the pandemic eliminated the achievement gap between urban and rural schools, making it statistically insignificant. Possible explanations for these results could be regional policies to support students or changes in examination procedures. These counterintuitive findings challenge the dominant educational research on COVID-19 and highlight the unexpected role of the pandemic in changing the trajectory of academic achievement.